Analisis Tingkat Hunian dari Persfektif Fasilitas Hotel di Nyiur Indah Beach Hotel Pangandaran - Indra, Dasril (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2018)
This study aims to obtain empirical evidence about "Occupancy Rate Analysis of Effect Study Perspective Hotel amenities Hotel amenities Decision Against guest to stay at Nyiur Indah Beach Hotel Pangandaran". The results are expected to provide benefits of this research is to determine the extent of the facilities owned by Nyiur Indah Beach hotel guests can attract traffic and increase hotel revenue. The method used is descriptive analysis and 'verification. Data collection is an interview with using a questionnaire accompanied by literature study. The sampling technique used is the non-probability sampling techniques that do not provide equal opportunity for each element or member of the population to be sampled. Field data collection conducted in 2015. Data were analyzed using Path. Analysis (Path Analysis). The results showed that there are significant positive and significant effect of the variable to variable-making facility stay. Indicators rooms were clean and comfortable is important in influencing a person to stay. Basically the reason someone stay dihotel is to rest, the rooms are clean and comfortable will make a guest feel at home and comfortable in the rest.